A history of the Good Shepherd School, Huntley Street, Grahamstown - Holshausen, Nicole (Rhodes University, Faculty of Education, Department of Education, 1999)
This thesis is a qualitative, historical study of The Good Shepherd School in Huntly Street, Grahamstown, South Africa. It is one of the oldest school buildings in South Africa that remains in use as a school. There are two main threads to understanding The Good Shepherd School in context. The first of these threads, the colonial root of the school, is explained in a discussion of the Grammar School, attached to the Cathedral of St. Michael and St. George, that utilised the Huntly Street facilities from 1851 to 1902. The second thread is the strong tradition of caring for the underprivileged. This is traced through following the development of the educational works of The Community of the Resurrection which involves the discussion of various schools at different locations in Grahamstown. The current school on the Huntly Street premises, The Good Shepherd School, forms, however, the focus of this study, which draws on all the histories of its forerunners and their historical locations. Historical social science methods and procedures were used in the research. This was done through documentary analysis of evidence as well as through semi-structured interviews, creating an interpretative account of how the school has affected people's lives. The conclusion reached is that The Good Shepherd School has contributed greatly to the education of underprivileged people in the Grahamstown area. It appears to be an outstanding example of a school offering a well-rounded, caring education when this was historically denied to many people in South Africa.
Keywords: Good Shepherd School (South Africa) -- History; Schools -- South Africa -- Eastern Cape; Schools -- South Africa -- Grahamstown